Results of the Prevention Program Dental Diseases in School-Age Children - Qurbonova Mahliyo Tavakalova; Burxonova Zarafruz Qobilovna; Yakubova Sarvinoz (Genius Journals, 2023)
This article describes the experience of conducting an educational program on oral care in Uzbekistan and the results of its implementation.
Keywords: Prevention; oral hygiene; sanitary and hygienic education